Transparency of State Owned Enterprises in Vietnam : Current Status and Ideas for Reform - World Bank (Washington, DC, 2014)
Information disclosure by State Owned Enterprises (SOEs) is part of a broader agenda to promote greater public sector transparency in Vietnam. Recent studies by the World Bank and others have shown that despite progress, compliance with legal requirements for transparency remains a challenge across a wide range of public sector governance areas in Vietnam. However, the marginal benefit to increased transparency is very significant. Timely availability of credible economic data, and better communication of policy changes, can help reduce market uncertainty and perceptions of risk. Transparency of SOEs is particularly important given their large presence in Vietnam s economy. In a survey conducted in 2011 for the Vietnam Development Report (2012) entitled Market Economy for a Middle Income Vietnam , improving transparency was cited by respondents as the top reform solution for SOEs in Vietnam together with accelerating equalization. Prime Minister s Decision 929 (2012), which sets out an overall plan to restructure General Corporations and State Economic Groups, sets out several commitments to help improve the transparency of SOEs. The SOE transparency agenda is an important part of the program supported under the Economic Management and Competitiveness Credit (EMCC) budget support operation. It is with this background that this Policy Note was prepared to help promote a dialogue between the Government of Vietnam and Development Partners on ways to enhance disclosure of information by SOEs.